Pengaruh Kualitas Pelayanan terhadap Volume Penjualan Usaha Toko Kopi Seduh - Fadilah, Nahar Zulfah; Supendi, Moh (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2024)
Changes in people’s lifstyles over time have had an impact on the business world. One of the businesses affected by the changes that have occurred is the coffee industry. The high level of coffee consumption in Indonesia causes businesses to take advantage of opportunities to open coffee shops. In facing competition, business actors must develop strategies that are oriented toward customer satisfaction. One of the factors that influence customer satisfaction is service quality. The better the quality of service provided, the more revenue the coffee shop business can increase. This research was conducted to determine the effect of service quality on sales volume. This research uses the associative quantitative method. The number of samples used was 100 samples with a probability sampling technique which was carried out at the Jagakarsa Seduh Coffee Shop. The data analysis technique uses the classic assumption test, namely the normality test, regression linearity test, simple regression analysis, correlation coefficient test and coefficient of determination, t statistical test. The result showed that service quality had a positive and significant effect of 43,2% on the sales volume of the Seduh Coffee Shop business. Therefore, coffee shop business actors should maintain and improve service quality to increase revenue in business sales volume.